Development of Low-Fat Soft Dough Biscuits Using Carbohydrate-Based Fat Replacers. (28th April 2013) - Chugh, Bhawna; Singh, Gurmukh; Kumbhar, B. K.
Abstract : Experiments were conducted to develop low-fat soft dough biscuits using carbohydrate-based fat replacers (maltodextrin and guar gum). A central composite rotatable design was used to optimise the level of sugar 24–36%, composite fat (fat 10.5–24.5%, maltodextrin 10.4–24%, and guar gum 0.1–0.5%), ammonium bicarbonate 0.5–2.5%, and water 20–24% for production of low-fat biscuits. Diameter( P < 0.01 ) and stress-strain ratio( P < 0.05 ) decreased significantly with increase in the amount of sugar. There was a significant decrease( P < 0.01 ) in spread ratio at high amount of water. Hardness was significantly affected by the interactions of ammonium bicarbonate with sugar( P < 0.05 ) and fat( P < 0.1 ) . The optimum level of ingredients obtained for low-fat biscuits was sugar 31.7 g, fat 13.55 g, maltodextrin 21.15 g, guar gum 0.3 g, ammonium bicarbonate 2.21 g, and water 21 mL based on 100 g flour. The fat level in the optimised low-fat biscuit formulation was found to be 8.48% as compared to 22.65% in control; therefore, the reduction in fat was 62.5%.